Ações afirmativas: a constitucionalidade da política de cotas para negros em universidades brasileiras - ALMEIDA, Thaiana Bitti de Oliveira (Universidade Federal do Pará, 2017)
The object of this work is to demonstrate the possibility of implement quota for black people in brazilian universities aiming to reach material equality throughout affirmative actions, as a way of minimalizing the consequences of historically cultivated prejudices that are still alive in our society under forms of discrimination. To accomplish this goal, we have proceeded to the analysis of the principle of equality and non-discrimination, linked to the principle of human dignity according to Ingo Sarlet's formulations. Afterwards, the theories of justice by John Rawls and Ronald Dworkin, named justice as equity and equity of resources, are studied as well as their relations with affirmative programs. Proceeding the research, we have studied the affirmative actions and the quota policies toward brazilian universities, tracing the characteristics of Brazil's academic population and highlighting the importance of equally ensuring the access to higher education. We analyze the criterion of justice, compatibility and efficacy identified by Brito Filho, the same ones that justify the implementation of quota and that are present in Ronald Dworkin's work, applying each of them to brazilian reality. Finally, we have demonstrated the quota policies' constitutionality in Brazil under the pluralist view about this subject that comes from Federal Supreme Court.